2012
DOI: 10.1111/j.1447-0594.2012.00910.x
|View full text |Cite
|
Sign up to set email alerts
|

Hospital treatment in residential care facilities is a viable alternative to hospital admission for selected patients

Abstract: Aim:  To determine if hospital treatment in residential care facilities, led by a geriatric team, might be a viable alternative to inpatient admission for selected patients. Methods:  Case series with a new intervention were compared with historical controls receiving the conventional treatment. Treatment in residential care facilities (TRC) by the Residential Care Intervention Program in The Elderly (RECIPE) service was compared against the conventional treatment group, aged care unit (ACU) inpatients. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 14 publications
1
35
0
Order By: Relevance
“…Lau et al compared outcomes of treatment in residential care and hospital inpatient treatment at different periods and found that treatment in residential care is a viable alternative for hospital treatment. However, in this study, hospital and home treatment groups were selected at different periods and hence time‐based factors could have affected the results.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Lau et al compared outcomes of treatment in residential care and hospital inpatient treatment at different periods and found that treatment in residential care is a viable alternative for hospital treatment. However, in this study, hospital and home treatment groups were selected at different periods and hence time‐based factors could have affected the results.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the study performed by Liu and McD Taylor used adverse events as defined by Harvard Medical Practice Study, whereas other studies defined adverse events as complications occurring related to VAD, pumps or drugs. A few studies considered 1 month after discharge for readmissions and mortality, some considered only during the treatment period and others considered 1 month or during therapy . These differences in reporting may contribute to the major differences in readmission, adverse events or mortality rates between studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent mental illness research concentrates on different areas that relate to the treatment of dementia such as: evidence-based practice (Lau et al, 2013;Nicholls et al, 2013;Ploeg et al, 2007;Stetler et al, 2009;Van Achterberg et al, 2008), educational aspects (Jeon et al, 2013), family involvement (Petriwskyj et al, 2014;Vreugdenhil, 2014), and funding impact and incentives (Jeon et al, 2013). However, there is a gap in research that focus on individual, customised aged care treatment care plans for mentally ill adults.…”
Section: Introductionmentioning
confidence: 99%